God’s Benevolent Love in the Time of COVID-19 Pandemic: Articulations and Experiences of Select Filipino Youth - Cacho, Rebecca (Religions, 2022)
Current studies show that the Christian faith is still robust in Philippine society and culture despite the global health crisis. This study investigates how select Filipino Christian youths intuited God’s benevolent love in the time of "social distancing" and how their experience of God’s benevolence helped them to carry on despite the COVID-19 pandemic. The authors administered open-ended survey questions about God’s love to select Filipino Christian youths. The responses were analyzed using thematic analysis and categorizations. Using contextual analysis, the researchers critically reflected upon the respondents’ notions of God’s love and religious experiences from the two poles of Filipino culture and Judeo-Christian tradition. According to select Filipino Christian youths, God is present and faithful. God’s "kagandahang-loob" (benevolent love) for human persons is evinced in the care and kindness of family members and neighbors. God also enables human persons to prevail over challenges in life, such as the COVID-19 pandemic. Moreover, God is the ultimate source of Christian hope. This hope is firmly anchored in Jesus Christ and the Church. Furthermore, God is forgiving and merciful. He continues to bless and give graces to human persons despite their sinfulness. These contemporary conceptualizations of God’s perfect interior goodness helped the select Filipino Christian youths cope with the COVID-19 pandemic.